COVID-19 Transmission and Clinical Features in Pediatric Intensive Care Health Care Workers - (:unkn) unknown (AVES, 2022)
Objective: This study aims to investigate modes of transmission and clinical features of coronavirus disease 2019 in healthcare workers in pediatric intensive care units. Materials and Methods: This multicenter descriptive study was conducted between March and November 2020. Patient demographics, clinical characteristics, origin of coronavirus disease 2019, treatment modalities, and loss of workdays were recorded. Results: Seven hundred and sixty-eight healthcare workers from 16 pediatric intensive care units were enrolled and 114 (14.8%) healthcare workers with a mean age of 29.7 +/- 6.7 years became coronavirus disease 2019 patients. Seventy-six (66.7%) patients were female. Approximately half (54.3%) of the patients were physicians, 34.2% were nurses, and 11.4% were ancillary staff. Transmission was deemed to occur through patient contact in 54.3% of the patients. Comorbid illness was present 10.5% of the patients. Transmission occurred during endotracheal intubation in 21%, cardiopulmonary resuscitation in 9.6%, and non-invasive ventilation in 12.2% of patients, while transmission was a result of multiple possible procedures in 43.8%. Intensive care admission was needed for 13.1% of the patients. Five patients needed oxygen by cannula, 7 needed oxygen with a non-rebreathing mask, 5 needed high-flow nasal cannula support, 5 needed non-invasive ventilation, and 3 needed invasive mechanical ventilation. Fortunately, no infected healthcare workers died. Conclusion: Coronavirus disease 2019 in healthcare workers is a significant problem in pediatric intensive care units. Transmission seems to occur particularly frequently during patient care procedures such as intubation, ventilation and aerosol therapy, which highlights the importance of proper use of full sets of personal protective equipment during all procedures during care of coronavirus disease 2019 patients.
Keywords: Children; COVID-19; health care worker; pediatric intensive care unit; SARS-CoV-2